Passion for Excellence My Lifelong Journey into Medicine and Public Service - Moutsopoulos, Haralampos M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This autobiography chronicles the life and career of Haralampos M. Moutsopoulos, an internationally renowned professor of medicine and prolific researcher on Sjögren s syndrome and autoimmune rheumatic diseases. In language that is simple and direct, he takes us on a fascinating journey from the days of his first scientific awakenings at a hospital in his native town of Ioannina, Greece, through his university years in Athens and training in the U.S., to his eventual return to his homeland. In Greece, he developed two centers of excellence in his field, first at the newly founded University of Ioannina Medical School Department of Internal Medicine and, second, at the Athens University Medical School, Department of Pathophysiology, where he taught until his retirement in 2011. Along the way, he introduces us to his teachers and mentors, and to the colleagues and students he mentored in turn, many of whom went on to assume high-ranking positions in Greece and abroad. A major theme throughout the book is his impassioned struggle for excellence, meritocracy, and transparency in universities and in the National Health System in Greece. Peppered with both amusing and unsettling incidents from this lifelong crusade to raise professional standards and against misconduct, the book is a must-read for anyone interested in learning about or entering the medical profession.
1. Coming of Age -- 2. Student Years -- 3. Young Physician -- 4. In the Army -- 5. Public Health Service.
Keywords: Rheumatology; Autoimmunity; Sociology Biographical methods; Rheumatology; Autoimmunity; Biographical Research; Autoimmune Diseases; Sjogren's Syndrome; Greece; Autobiography